Lipase Mediated Hydrolysis Of Crude Palm Oil In Enzymatic Membrane Reactor And Recovery Of Carotenes And Tocopherol - Serri, Noor Aziah (2012)
Production of fatty acid and glycerol from oils are important especially in oleochemical industries. Nowadays, researchers prefer to use enzyme to conduct hydrolysis in order to reduce energy consumption and minimize thermal degradation of the products. The advantages of the enzyme hydrolysis technique include; the use of bio-route technology that only requires a mild temperature, simple operational procedure and low cost as well as energy consumption. The present investigation focuses on hydrolysis of triglyceride to produce free fatty acids and glycerol from crude palm oil (CPO) using Candida rugosa lipase in batch and enzymatic membrane reactor (EMR). At the same time, the recovery of carotenes and tocopherol was also studied. The optimization in hydrolysis of CPO for batch process was carried out using Design of Experiment that focuses on response surface methodology (RSM) to optimize the hydrolysis reaction. The process variables which were taken into account include; enzyme loading, A (0.30 – 0.80 g), oil loading, B (0.15 – 0.35 g/ml), reaction temperature, C (40oC - 50oC) and pH of buffer solution D, (6.5-7.5). The optimum conditions found for the enzymatic hydrolysis of CPO under investigation are: 0.43 grams of enzyme, 0.15 g/ml of oil with temperature of 45oC and buffer solutions at pH 7.0. The yield predicted for fatty acids produced can reach up to 90.95% and the actual value was found to be 90.67% (5.59 x 10-5 mol hr-1 g-1 enzyme).